Evaluasi Penggunaan Obat Sitostatika Ditinjau Dari Berbagai Literatur - Nurwulan Adi Ismaya; Riris Andriati; Tri Okta Ratnaningtyas; Nur Hasanah; Dewi Yulianti (STIKes Kharisma Persada, 2021)
Cancer is a non-communicable disease, or NCD (Noncommunicable diseases). It becomes a second causative factor of mortality in global. In some cases and scientific journals that show a high problem of drug use in cancer patients. The purpose of this research is to identify the use of sitostatica drugs which are reviewed from a variety of literature. This study uses literature study research. Literature study is a research conducted by researchers by collecting a number of library data relating to the problem and research objectives. Result showed there are the most inaccurate drug diagnosis criteria for patients are 16 cases (22.86%). Inaccuracy in most doses is 21 cases (29.18%). the most inaccurate dose inaccuracy is 127 cases (36.38%), inaccurate indications include the need to add drugs the most is 26 cases (25.49%), drugs without the most indications are 11 cases (10.78%) , inaccurate duration of administration of the most drugs is 15 cases (23.43%), the criteria for alerting for the most side effects are 208 cases (59.59%) the right criteria for the administration method is 100%, the patient is 100% right, and the right submission (dispensing) and information at 100%.